Photocatalysis: Tailor‐Made Photoconductive Pyrene‐Based Covalent Organic Frameworks for Visible‐Light Driven Hydrogen Generation (Adv. Energy Mater. 24/2018). Issue 24 (27th August 2018) - Stegbauer, Linus; Zech, Sebastian; Savasci, Gökcen; Banerjee, Tanmay; Podjaski, Filip; Schwinghammer, Katharina; Ochsenfeld, Christian; Lotsch, Bettina V.
Abstract : In article number 1703278, Bettina Lotsch and co‐workers highlight the importance of unravelling structure – property – activity relationships in a series of pyrene‐based COFs with trending optoelectronic properties and demonstrate their potential for photoelectrochemical hydrogen evolution. Image by Christoph Hohmann, Nanosystems Initiative Munich (NIM).